Energetic and exergetic assessments of glycerol steam reforming in a combined power plant for hydrogen production. (14th September 2015) - Rabbani, M.; Dincer, I.
Abstract This paper presents a thermodynamic analysis of a steam reformer coupled with a combined power plant to produce hydrogen from steam and hydrocarbon fuel. In the analysis, the steam reformer uses glycerol as a fuel and produces hydrogen for high temperature proton exchange fuel cells in which the catalyst is tolerant to the amount of carbon monoxide. The results show that increasing the steam to glycerol ratio increases the hydrogen production. However, it decreases the overall efficiency of the system because of the high heat input requirement to the system. Numerous operating conditions and plant parameters are varied and their effects on the overall energy and exergy efficiencies of the system are studied. An optimization study is performed in order to find the optimal system parameters for better performance.